Corruption and women in cabinets: Informal barriers to recruitment in the executive. Issue 1 (16th July 2018) - Stockemer, Daniel; Sundström, Aksel
Abstract : Research on corruption and women in politics has mainly focused on legislatures, generally finding that corruption decreases the election of women. This article turns the spotlight to the executive branch—an arena where selection is less transparent than recruitment to legislative seats—and examines if corruption decrease the share of ministers who are women. Drawing on feminist institutionalist theories, we posit that in an environment of high political corruption, (male) elites involved in cabinet formation will tend to appoint ministers whom they can trust with secretive tasks. In systems with corrupt networks, relative newcomers, such as women, should face obstacles to career advancement. The article tests this reasoning empirically on a global sample of countries across time. Using a new indicator measuring corruption in executive bodies, we find support for our argument; corruption tends to hinder women's presence in cabinets, albeit only in democracies and not autocracies.